2020
DOI: 10.4097/kja.19475
|View full text |Cite
|
Sign up to set email alerts
|

Discovering hidden information in biosignals from patients using artificial intelligence

Abstract: Biosignals such as electrocardiogram or photoplethysmogram are widely used for determining and monitoring the medical condition of patients. It was recently discovered that more information could be gathered from biosignals by applying artificial intelligence (AI). At present, one of the most impactful advancements in AI is deep learning. Deep learning-based models can extract important features from raw data without feature engineering by humans, provided the amount of data is sufficient. This AI-enabled feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Recently, several studies have been successful in estimating clinical information that was not explicitly provided, such as in the prediction of valve disease or hyperkalemia using deep learning in electrocardiogram studies ( Galloway et al, 2019 ; Kwon et al, 2020 ). This supports the hypothesis that hidden but clinically meaningful information may exist in bio-signals, and these patterns could be analyzed with deep learning methods ( Yoon et al, 2020 ).…”
Section: Discussionsupporting
confidence: 81%
“…Recently, several studies have been successful in estimating clinical information that was not explicitly provided, such as in the prediction of valve disease or hyperkalemia using deep learning in electrocardiogram studies ( Galloway et al, 2019 ; Kwon et al, 2020 ). This supports the hypothesis that hidden but clinically meaningful information may exist in bio-signals, and these patterns could be analyzed with deep learning methods ( Yoon et al, 2020 ).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have suggested that clinically important information remained undiscovered in the biosignal data [83,84]. In the ECG waveform data, atrial fibrillation could be detected regardless of whether the ECG waveforms maintained normal sinus rhythm [48].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning, which can learn patterns from data, is the most widely used AI algorithm in perioperative medicine [ 11 ]. Machine learning algorithms are typically classified into three categories: supervised, unsupervised, and reinforcement learning ( Fig.…”
Section: Overview Of Ai Techniquesmentioning
confidence: 99%
“…Accurate perioperative risk stratification is important for facilitating shared decision-making and the allocation of medical resources. Several preoperative risk scores have been developed and used in clinical practice, including the American Society of Anesthesiologists Physical Status (ASA-PS) classification [ 11 ], American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) surgical risk calculator [ 25 ], surgical Apgar score [ 26 ], and Risk Stratification Index [ 27 ].…”
Section: Ai Models For Perioperative Risk Stratificationmentioning
confidence: 99%